KONSTRUKSI SOSIAL DAN LIVING QUR’AN DALAM TRADISI PEGON MASYARAKAT AMBULU KABUPATEN JEMBER - Vida Miladiah (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
The pegon tradition which is carried out every seventh day during Eid al-Fitr is an activity that has been passed down from generation to generation. This study examines the Pegon Tradition which is relevant to the living Qur'an and the perspective of social construction is reviewed using Peter L Berger's theory. The pegon tradition has undergone a long process and religious acculturation has experienced significant development influenced by the presence of the Living Qur'an in the community and it is known that the reciprocal process with the environment occurs in Ambulu residents through the reading of the letters al-Fatihah, al-Waqiah and al-Mu'awidzatain carried out by residents indicating that social construction has been formed. The results of this study are the presence of the Living Qur'an with a communal-massive community category indicating that there is an acculturation phenomenon that occurs in the implementation of the Pegon Tradition which has similarities with larung sesaji, but the difference lies in the way it is implemented. This is a form of gratitude for the sea products initiated by religious figures to change the habits of residents in the tradition by asking for prayers for protection from Allah SWT. The social construction in the implementation of the Pegon Tradition goes through three processes, namely externalization, objectivation, and internalization. This then made the pegon tradition maintained until now as an internalization process and became a routine activity every year.